Case Report: Keratoacanthoma and type I diabetes secondary to treatment with PM8001, a bifunctional fusion protein targeting TGF-β and PD-L1 - Qi, Rongbin; Xu, Hailing; Fu, Xinyu; Yu, Yingying; Lv, Dongqing; Li, Yujing; He, Susu (Frontiers in Oncology, 2023)
ABSTRACT：Immune related adverse reactions mainly involve the skin, endocrine system, digestive system and respiratory system, etc. Among them, endocrine related immune related adverse effects mainly include hypophysitis, thyroiditis, hypoadrenalism and diabetes mellitus, among which type I diabetes mellitus is one of the rare types. The most common immune related toxicities of the skin are pruritus and rash, while eruptive keratoacanthoma is its rare type. We report a case of a 67 year old woman who developed eruptive keratoacanthoma of the skin at week 6 after initiation of treatment with a bispecific antibody (PM8001) that can simultaneously target PD-1 and TGF-β and continued treatment for type I diabetes mellitus induced ketoacidosis at week 13. Type I diabetes tends to stabilize after insulin treatment, and keratoacanthoma gradually returns to normal after discontinuation of the drug. By describing a case of PM8001 immunotherapy involving endocrine glands and skin and reviewing relevant literature, we were able to summarize the clinical characteristics of rare immune related adverse events (irAEs) resulting from PM8001 immunotherapy for early detection, diagnosis, and treatment.